Governance of Visibility Platform - Slawomir Wycislak (International Journal of Supply Chain Management, 2021)
A real-time transportation visibility platform develops its network by adding successive complementors. The governance mechanism benefits the platform owner the most and creates asymmetries among platform members. These asymmetries trigger coopetition tensions between governance costs and co-created value, autonomy, and control. Resolving tensions between complementors and real-time visibility platform provider is a key for the successful performance of a real-time visibility transportation platform. The fee share and bonus malus scheme should balance the asymmetries of benefits from being part of a real-time visibility transportation platform.